UMP making heads turn with a string of recent recognitions - T.N., Alagesh (New Straits Times, 2023)
KUANTAN: Universiti Malaysia Pahang (UMP) has joined the list of world's elite higher learning institutions after six subjects offered at the campus here are listed in the QS World University Rankings by Subjects 2023.